1991
DOI: 10.1093/nar/19.8.1965-a
|View full text |Cite
|
Sign up to set email alerts
|

KpnI and RsaI RFLPs for the human fumarylacetoacetate hydrolase (FAH) gene

Abstract: Source and Description of Clone: The probe phHAC is a 480 bp PstI/EcoRI fragment from the 3' end of phHA2, a 1.5 kb human fumarylacetoacetate hydrolase cDNA clone containing all the FAH coding sequence (1). Polymorphism: Bglll detects a three-allele polymorphism with variant fragments of 16.4 kb (DI), 12.7 kb (D2) and 6.6 kb (D3). One constant band is present at 3.0 kb. Frequency: Estimated from 35 unrelated (at least at the second degree) French-Canadian individuals. Dl: 0.25 D2: 0.38 D3: 0.37 Heterozygosity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
1992
1992

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Introduction of the human FAH cDNA into CV-1 monkey kidney cells resulted in the synthesis of a fully functional enzyme, indicating that the encoded sequence contained all the genetic information necessary for the hydrolytic activity ( 14). We mapped the structural gene for human FAH to the long arm of chromosome 15 in the region q23-25 (14) and identified restriction site polymorphisms at the FAH locus in normal humans (16)(17)(18)(19) Sequence analysis ofthis cDNA identified an A47 to T transversion that predicted an asparagine to isoleucine substitution at codon 16 (N161). Amplification and sequencing of this specific region on genomic DNA suggested that the patient is a genetic compound.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of the human FAH cDNA into CV-1 monkey kidney cells resulted in the synthesis of a fully functional enzyme, indicating that the encoded sequence contained all the genetic information necessary for the hydrolytic activity ( 14). We mapped the structural gene for human FAH to the long arm of chromosome 15 in the region q23-25 (14) and identified restriction site polymorphisms at the FAH locus in normal humans (16)(17)(18)(19) Sequence analysis ofthis cDNA identified an A47 to T transversion that predicted an asparagine to isoleucine substitution at codon 16 (N161). Amplification and sequencing of this specific region on genomic DNA suggested that the patient is a genetic compound.…”
Section: Introductionmentioning
confidence: 99%